Hubungan Antara Perhatian Orang Tua dan Fasilitas Belajar dengan Prestasi Belajar Siswa - Onny, Fariha (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2021)
This study aims to determine the relationship between the variables of parental attention (X1) and learning facilities (X2) on student achievement (Y). This research is a type of descriptive and expost facto research. The population in this study were all first grade students of SMA Negeri 11 Semarang, South Semarang, Semarang City, Central Java, which consisted of 15 classes with a total of 430 students. The research sample was taken by random sampling, namely two classes were taken with a total of 70 students. The data collection method is a questionnaire to obtain data on parental attention and learning facilities, and documentation for learning achievement data. The data analysis technique used a regression analysis equation of two independent variables. The results of the analysis obtained the multiple regression equation Yˆ = 4.698 + 0.01X + 0.1X, and the coefficient of determination was 0.163 or 16.3%. This means that the contribution of the variables of parental attention and learning facilities together on student achievement at SMA Negeri 11 Semarang, South Semarang, Semarang City, Central Java is 16.3%, through the regression equation. Furthermore, the significance was tested using the F test. It turned out that FCount was 6.505 greater than FTable with dk = 67 and a significant level of 5% was 3.140. This means that the multiple regression model obtained can be used to predict learning achievement. Based on the data analysis, it can be explained that there is a positive and significant relationship between parental attention and learning facilities together with the learning achievement of first grade students at SMA Negeri 11 Semarang, South Semarang, Semarang City, Central Java.